(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
The study of gender-specific speech deficiencies in children offers valuable insights into the interplay between cognitive development, socialization processes, and linguistic performance. Drawing upon a comparative analysis of Uzbek and English data, this paper investigates the distinctive speech shortcomings observed in boys’ and girls’ language use, highlighting their linguistic, psycholinguistic, and socio-cultural determinants. The paper synthesizes empirical observations with theoretical perspectives from gender linguistics, discourse analysis, and child language acquisition research. Special attention is given to the ways in which these deficiencies manifest in phonetic, lexical-semantic, and pragmatic domains, as well as to effective strategies for remediation. The study demonstrates that speech deficiencies are not merely individual cognitive limitations but are embedded within culturally mediated communicative norms and gender-specific interactional patterns. The proposed remedial approaches emphasize an integrated methodology that accounts for linguistic structure, discourse environment, and socio-emotional context.